Potential of Microalgae as Biofuel Feedstock - Dwicahyanto, Sharfan; Parviana, Yunita; Novtiansyah, Ditra (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2017)
Microalgae are photosynthetic microorganism capable to produce biomass fraction such as lipids, proteins and carbohydrates. Microalgal biomass can be converted to biofuel such as bioethanol, biodiesel and biogas. Biofuel derived from microalgae considered as third generation of biofuel. Microalgal biomass can be converted to energy by biological or chemical methods. Carbohydrate-enriched microalgal biomass can be used for bioethanol raw material. Biomass with high carbohydrate content can be made by manipulating environment factors such as cultivation medium, nutrition limitation, light intensity, salt stress, and temperatures. Biofuel derived from microalgal can replace biofuel derived from terrestrial plants because microalgal biomass has a high caloric value, low viscosity, low density, and lack of lignin that make it easy for converting it into biofuel like bioethanol